2015
DOI: 10.1074/jbc.m115.668293
|View full text |Cite
|
Sign up to set email alerts
|

The Polarized Effect of Intracellular Calcium on the Renal Epithelial Sodium Channel Occurs as a Result of Subcellular Calcium Signaling Domains Maintained by Mitochondria

Abstract: Background: Mitochondria can sequester calcium and regulate signaling processes in epithelia. Results: Intracellular calcium regulates the renal epithelial sodium channel in a polarized fashion, and this polarity is dependent on mitochondrial calcium uptake. Conclusion: Mitochondria maintain calcium polarity in renal epithelia. Significance: Identifying subcellular calcium signaling domains in renal epithelia is essential to understanding ion channel regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Multiple studies have shown ENaC is regulated by calcium [19, 32, 33]. We previously showed calcium in concert with calmodulin inhibits the MARCKS mediated PIP2 dependent regulation of ENaC [19].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown ENaC is regulated by calcium [19, 32, 33]. We previously showed calcium in concert with calmodulin inhibits the MARCKS mediated PIP2 dependent regulation of ENaC [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a strong elevation of intracellular Ca 2ϩ (Ͼ 1 M) is required to activate TRPM4 (13,21). Our data indicate that the Ca 2ϩ sensitivity of TRPM4 channels in the cultured mpkCCD c14 cells is even lower than those previously reported in other cell types, which has an EC 50 of 32.6 M. Our recent studies suggest that mitochondria can form a band below the apical membrane of CCD principal cells to function as a Ca 2ϩ barrier (34). This mitochondria band may take up the released Ca 2ϩ which is induced by ATP before it diffuses to the apical membrane where the channel is located.…”
Section: Discussionmentioning
confidence: 50%
“…It should be noted that Shaughnessy et al [ 54 ] observed that listeriolysin O pores generated by the bacterium in the process of primary vacuolar escape allow Ca 2+ in the vacuole to leak into the cytoplasm, albeit slowly. It is possible that calcium binding promotes changes in InlP behavior that are specific to different calcium microdomains in the polarized epithelium [ 55 , 56 ], including microdomains potentially specific to basal protrusions and/or placental trophoblasts [ 57 ].…”
Section: Discussionmentioning
confidence: 99%